TINJAUAN YURIDIS BELIS TERHADAP SYARAT PERKAWINAN MASYARAKAT ADAT MANGGARAI (STUDI KASUS PADA MASYARAKAT DI DESA KETANG): Juricical Review Of Belis As A Condition Of Marriage In The Manggarai Indigenous Community (Case Study Of The Community In Ketang Village) - Stella Amanda Marcella W; Simona Bustani (Faculty of Law, Universitas Trisakti, 2025)
In general society, people often meet, interact, and mingle, making it possible for everyone to form a family unit, which is referred to as marriage, regulated under family law or kinship law. Marriage is an issue that concerns the entire community of customary unions. This study identifies the issue regarding marriage influenced by customs or traditions of certain regions within communities or kinship relations maintained by society. In the marriage process throughout Indonesia, traditions are deeply rooted and trusted from generation to generation. This is due to the strength of traditions passed down, believed by Indonesian society as something that must be upheld. One aspect attracting attention in marriage culture is the dowry given by the groom to the bride. Ketang Village, Lelak District, East Nusa Tenggara applies belis as an important tradition and a prerequisite for marriage. Belis is a dowry given by the groom’s family (anak wina) to the bride’s family (anak rona). If belis cannot be fulfilled, the marriage fails, and based on the findings and conclusion, it is found that the excessive demand for belis often leads to the failure of marriage.